Pengaruh Pertumbuhan Ekonomi dan Kemiskinan Terhadap Ketimpangan Pendapatan di Sumatera Utara Periode 2015-2019 - Dinda Syahri; Yesy Gustiara (Journal of Trends Economics and Accounting Research, 2020)
One of the causes of income inequality is the large number of poor people and uneven economic development. The triangular relationship between poverty, economic growth and inequality shows a continuous interaction between these three factors, with the aim of knowing the impact of economic growth and poverty in North Sumatra. The impact of income inequality in the period 2015-2019, the research method used is a quantitative method using multiple linear regression techniques. The data used is secondary data obtained from the Central Statistics Agency for the 2015-2019 period of North Sumatra. The results of this study indicate that economic growth has a positive and insignificant effect on income inequality in North Sumatra. Poverty has a negative effect on income inequality in North Sumatra, while economic growth and poverty have an impact on income inequality in North Sumatra. This had an impact during 2015-2019.